2022
DOI: 10.1590/2317-1782/20212021076
|View full text |Cite
|
Sign up to set email alerts
|

Suplementação com açaí (Euterpe Oleracea Martius) para o tratamento do zumbido crônico: efeitos na percepção, níveis de ansiedade e biomarcadores de metabolismo oxidativo

Abstract: RESUMO Objetivo Investigar os efeitos da suplementação antioxidante com extrato de açaí no incômodo com o zumbido crônico e a relação com os níveis de ansiedade e metabolismo oxidativo, não excluindo a sobreposição de enfermidades. Método Ensaio clínico, randomizado, controlado por placebo. Participaram 30 indivíduos, com média de 50,5 anos, 14 do sexo masculino e 16 do feminino, com limiares auditivos normais ou perda auditiva sensorioneural até grau leve bilateralmente, divididos em dois grupos: Grupo Plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…However, there was no significant difference with the placebo, probably due to a strong response in this arm. Another randomized controlled trial reported a 10.0-point reduction in THI score after 3 months' consumption of 100 mg of the higher antioxidant-rich extract of Euterpe oleracea martius (Açaí) once a day [32]. Overall, these results provide clinical evidence for the use of antioxidant molecules in tinnitus that should not be ignored.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, there was no significant difference with the placebo, probably due to a strong response in this arm. Another randomized controlled trial reported a 10.0-point reduction in THI score after 3 months' consumption of 100 mg of the higher antioxidant-rich extract of Euterpe oleracea martius (Açaí) once a day [32]. Overall, these results provide clinical evidence for the use of antioxidant molecules in tinnitus that should not be ignored.…”
Section: Discussionmentioning
confidence: 83%
“…THI score changes from baseline at 3 months was chosen as meaningful primary endpoint. The Tinnitus Handicap Inventory [22] and its French version [24] is a 25-item self-report measure to determine perceived tinnitus handicap severity which is classified as very mild (score 0-16), mild (score [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], moderate (score 38-56), severe (score 58-76), and catastrophic (78-90). A change in score of at least seven points has been considered to denote reliable clinically significant improvement on the THI [26].…”
Section: Methodsmentioning
confidence: 99%
“…However, there was no significant difference with placebo, probably due to a strong response in this arm. Another randomized controlled trial reported a 10.0-point reduction in THI score after 3 months' consumption of 100 mg of the higher antioxidant-rich extract of Euterpe oleracea martius (Açaí) once a day [32]. Overall, these results provide clinical evidence for antioxidant molecules in tinnitus that should not be ignored.…”
Section: Discussionmentioning
confidence: 84%
“…Antioxidant therapy in patients with idiopathic tinnitus could reduce oxidative stress and damage to the inner ear, also reducing tinnitus loudness and discomfort. However, research data on the efficacy of antioxidant supplementation in tinnitus are scarce and conflicting, although there are some recent reports that show tinnitus improvement after treatment with antioxidants ( Procházková et al, 2018 ; Oppitz et al, 2022 ). Additionally, emerging evidence suggests that neuroinflammation may play a large role in the development of tinnitus and the influence of various proinflammatory cytokines such as TNF-α, IL-6, β-2GP1 and IL-1 has been described.…”
Section: Discussionmentioning
confidence: 99%